Governing through resilience? Exploring flood protection in Dresden, Germany. - Hutter, Gérard; Leibenath, Markus; Mattissek, Annika (MDPI, 2014)
The paper argues for a governmentality perspective on risk-management politics and resilience-related governance. This perspective pays ample attention to conflicts and discursive 'battles' in which different truths and normative assessments, including specific rationalities, subjectivities and technologies of governing compete against. Up to now, the literature on governmentality and resilience has mainly been based on empirical research in the UK. This research highlights the growing importance of neoliberal forms of governing, including a shift in governing strategies towards activating and responsibilizing the public. This is to some extent in contrast to observations about dealing with flood risk on the river Weisseritz in Dresden. The paper reflects on possible avenues for further conceptual and empirical research on 'governing through resilience' in the context of flood protection in Germany. It is based on a brief conceptualization of 'governmentality' as introduced by Michel Foucault, a literature review, and selected observations from a case study on flood protection for the river Weisseritz in Dresden.
Keywords: Planungstheorie; Überschwemmung; Hochwasserschutz; Risikoanalyse; Kommunikation; Partizipation; Governance; Risikokommunikation